2021
DOI: 10.1101/2021.08.08.21261766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity of BNT162b2 vaccine Against the Alpha and Delta Variants in Immunocompromised Patients

Abstract: Background. The emergence of strains of SARS-CoV-2 exhibiting increase viral fitness and immune escape potential, such as the Delta variant (B.1.617.2), raises concerns in immunocompromised patients. To what extent Delta evades vaccine-induced immunity in immunocompromised individuals with systemic inflammatory diseases remains unclear. Methods. We conducted a prospective study in patients with systemic inflammatory diseases (cases) and controls receiving two doses of BNT162b2. Primary end points were anti-sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Although antibody response also peaks at 2 weeks 5 , antibody levels provided limited predictiveness for the T-cell clonal response induced by vaccination, particularly for individuals with a low T-cell response. This is consistent with findings reported from polyfunctional T-cell assessment 10 , 11 , 13 , 14 . In the context of reimmunization strategies, T-cell assessment may be important to evaluate both initial vaccine response and persistence of immunity after vaccination 15 , 16 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although antibody response also peaks at 2 weeks 5 , antibody levels provided limited predictiveness for the T-cell clonal response induced by vaccination, particularly for individuals with a low T-cell response. This is consistent with findings reported from polyfunctional T-cell assessment 10 , 11 , 13 , 14 . In the context of reimmunization strategies, T-cell assessment may be important to evaluate both initial vaccine response and persistence of immunity after vaccination 15 , 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Interrogation of our IBD patient cohort permitted assessment under select and discrete modes of therapeutic immunosuppression. Few studies have assessed the T-cell response to SARS-CoV-2 vaccines, and with few exceptions 12 have used methods that enumerate SARS-CoV-2-specific T-cells based on peptide-stimulated cytokine production 10 , 11 , 13 , 14 . Such studies don’t permit assessment of repertoire diversity and clonal size, important factors in protective T-cell immunity 3 , 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Study characteristics of the included publications6–13 25–39 are summarised in table 1. Information to assay details of antibody detection and CMI are indicated in online supplemental appendix, pp.…”
Section: Resultsmentioning
confidence: 99%
“…We defined SARS-CoV-2 vaccine elicited humoral immune response as detection of antispike antibodies (anti-RBD or anti-S1 (spike protein) SARS-CoV-2) above the cut-off reported by the manufacturer of the given assay. Vaccine elicited cell-mediated immune response was defined as detection of SARS-CoV-2 specific T cells either measured by, T-EliSpot,6–9 interferon-γ release assays10 11 or activation-induced marker (AIM) detection12 13 in flow cytometry-sorted cells. AIM used for the detection of vaccine elicited T cells response were CD4 +CXCR5+PD1+and CD38+HLA-DR+12 as well as S-specific OX40 +41-BB+CD4+ and CD69+41BB+CD8+ 13…”
Section: Methodsmentioning
confidence: 99%
“…However, whether gender is the factor to affect the immunization remains controversial (90,91). In immunocompromised individuals receiving immunosuppressive drugs, Hadjadj et al observed that antibody responses had partial neutralizing activity against Alpha, and even weaker against Delta stains, and their T cell responses were also altered (92). Therefore, immunosuppressive drugs for specific diseases might affect the vaccine-induced immunological effects.…”
Section: Bnt162b2 Mrna Vaccinementioning
confidence: 99%